How Many Years Have Refugees Been in Exile? - Devictor, Xavier; Do, Quy-Toan (World Bank, Washington, DC, 2016)
The estimated duration of forced displacement situations is a key parameter in defining an adequate response to the crisis. Where the crisis is short, humanitarian aid may suffice; when it lasts, development interventions are required. Using data from the United Nations High Commissioner for Refugees, this paper proposes propose a new approach to estimate the mean and median durations of exile, and their variations over time. The analysis finds that people who were refugees at the end of 2015 have been in exile for an average duration of 10.3 years and a median duration of 4 years; the average duration of exile has varied between 10 and 15 years since the late 1990s. The number of people who are in protracted situations (over five years) has been steady at 5 million to 7 million since the mid-1990s, and currently stands at 6.6 million. For those people, the average duration of exile is as long as 21.2 years. All these estimates are very sensitive to two situations: Afghanistan, where the crisis has been ongoing since 1979 and increases all averages, and the Syrian Arab Republic, which is relatively recent and lowers the averages.